A critical look at evidence from La Chapelle-aux-Saints supporting an intentional Neandertal burial. (January 2015) - Dibble, Harold L.; Aldeias, Vera; Goldberg, Paul; McPherron, Shannon P.; Sandgathe, Dennis; Steele, Teresa E.
Abstract: In a paper based on recent excavations and analysis of recovered material at the French Middle Paleolithic site of La Chapelle-aux-Saints, Rendu et al. (2014) concluded that there is sufficient evidence to support the long-held interpretation that the Neandertal remains found in the bouffia Bonneval locality represents an intentional Neandertal burial. This paper critically examines their data and arguments in relation to criteria that can be used to provide an objective evaluation of such evidence. In each case, the evidence from La Chapelle-aux-Saints either fails to meet these criteria or supports other interpretations equally well. As a result, this site fails to provide unequivocal evidence in support of the notion that Neandertals intentionally interred their dead, whether in any ritualistic or symbolic context or not. Highlights: Recent work at the site of La Chapelle-aux-Saints has re-affirmed its status as a Neandertal burial site. However, the available evidence still does not meet many of the criteria of an intentional interment. At this time, the case of La Chapelle is ambiguous, at best, regarding the question of deliberate Neandertal burials. This study points to the need of further studies of preservation under varying circumstances.